1998
DOI: 10.1128/jcm.36.9.2439-2442.1998
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the RapID CB Plus System for Identification of Coryneform Bacteria andListeriaspp

Abstract: In a stress test, the recently introduced RapID CB Plus system (Remel Inc. [formerly Innovative Diagnostic Systems], Norcross, Ga.) was challenged with a diverse set of gram-positive rods comprising 345 strains of coryneform bacteria and 33 strains of Listeriaspp. representing a total of 49 different taxa. Overall, within 4 h, the system correctly identified 80.9% of the strains on the species level and 12.2% of the strains on the genus level. Only 3.7% strains were misidentified, and for 3.2% of the strains n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…RapID CB Plus system is composed of 4 carbohydrate utilization tests and 15 enzymatic tests and identifies 23 Corynebacterium species (Funke et al . ). Evaluation of these two systems revealed that 97·6 and 95% of strains, respectively, were identified correctly (Freney et al .…”
Section: Manual Biochemical Identification Systemsmentioning
confidence: 97%
See 2 more Smart Citations
“…RapID CB Plus system is composed of 4 carbohydrate utilization tests and 15 enzymatic tests and identifies 23 Corynebacterium species (Funke et al . ). Evaluation of these two systems revealed that 97·6 and 95% of strains, respectively, were identified correctly (Freney et al .…”
Section: Manual Biochemical Identification Systemsmentioning
confidence: 97%
“…6 standard for API Coryne system), hence, it is often impossible to identify coryneform bacteria directly from primary growth plates (Funke et al . ).…”
Section: Manual Biochemical Identification Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the API-Coryne system (bioMérieux) all three yield the code 2100004; thus, additional tests (CAMP, DNase, APIZYM reactions) are required. The VITEK 2 ANC card (bio-Mérieux) most likely also requires additional tests [18]. The RapID CB Plus system (Remel, Inc., Lenexa, KS, USA) correctly identified T. otitidis and C. auris but not C. afermentans to the species level [17].…”
Section: Laboratory Diagnosismentioning
confidence: 99%
“…Kligler's or triple sugar iron agar should also be inoculated. In lieu of single tests, commercial identification systems such as API Coryne v.2 [22] or RapID CB Plus (Remel Inc., Norcross, GA, USA) [23] may be used; both contain R. dentocariosa in their data bases. Directions for use must be followed strictly.…”
Section: D E N T I F I C a T I O N O F R D E N T O C A R I O S A mentioning
confidence: 99%